PENGARUH MODEL PEMBELAJARAN THINK-PAIR-SHARE DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN LITERASI SAINS SISWA SEKOLAH DASAR : Penelitian ini menggunakan pendekatan kuantitatif dengan desain pre-experemintal one group pretest-posttest - farhan suhaidi; Darmiany Darmiany; Ida Ermiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of the Thinking-Pair-Share (TPS) learning model and learning motivation on the scientific literacy learning ability of elementary school students. The low scientific literacy of students is reflected in the results of national assessments and PISA studies showing the existence of learning strategies that can increase the active involvement of students and encourage collaborative knowledge construction. This study uses a quantitative approach with a pre-experimental one group pretest-posttest design. The research 6subjects were 29 fifth grade students of SDN 5 BANYUMULEK. Learning motivation data were collected through test and answer instruments, then analyzed using the Kolmogorov-Smirnov and Shapiro-Wilk normality tests and paired sample t-tests. The results showed that all data were normally distributed so that they met the requirements of parametric analysis. The TPS model provides opportunities for students to think independently, discuss in pairs and share ideas in groups, thereby strengthening critical thinking skills, communication and conceptual understanding. Thus, the TPS model can be used as an alternative science learning strategy to improve scientific literacy while simultaneo*usly fostering students' learning motivation.